Geomagnetic disturbances at Akademik Vernadsky during magnetic clouds in 1997 - Maksymenko, O. I.; Melnyk, G. V.; Yaremenko, L. N.; Mozgovaya, T. A. (Ukrainian Antarctic Journal, 2005)
The comparative studying of Dst-variations and temporal variations of solar wind (SW) and interplanetary magnetic field (IMF) parameters during the 9 magnetic disturbances in 1997 were carried out to define the geoeffective condition in the magnetic clouds (MC). The logarithm type relation between the Dstmin index and energy input into the magnetosphere were found during MC with a large rotation of the magnetic field vector and vast solar wind velocity (more 400 km/c). It was shown that the empirical dependence of Dstmin index variations upon the cosine of the observatory latitude breaks down for American sector and modelling of the Dst-variation field are indispensable for understanding the appearances of the 10 degrees located positive 2Dstmin anomaly on high latitudes during main phase of the great magnetic storm on May 15, 1997 on the dayside of the Earth.